Bergson's GIS: Experience, Time and Memory in Geographical Information Systems - Rob Shields (Media Theory)
Geographical Information Systems (GIS) intended as digital forms of mapping struggle to represent time, change and temporality. The assumption of a static Cartesian, metric space of two or three dimensions only and defined by coordinates makes it difficult to create GIS and Historical GIS (HGIS) interfaces and representations that include the dynamics Bergson and later Deleuze describe. They argue that temporal memory is the basis of attention in encounters and perception of situations. This “affiliation” of the past enlivens the present perceptual life of experience. Video gaming and the combination of Google Earth and Street View are explored as limited alternatives that draw on embodied, kinaesthetic experiences of movement in space to open up or “uncurl” extra dimensions that allow more nuance in digital representations of spatiotemporal encounters, and the many modes and rhythms of duration found in the environment.